Histopathological evaluation of placenta in low-birth-weight babies at a tertiary care center of Nepal - Binaya Shrestha; Ramesh Makaju; Sunila Shakya; Dipika Basnet; Binod Dhakal; Nikita Gautam (Janaki Medical College Journal of Medical Science, 2024)
Background & Objectives: Pregnancy-related death and morbidity rates are significantly impacted by the prenatal care provided to expectant mothers. Low birth weight (LBW) is the single most important factor among the several causes of perinatal mortality; consequently, placentas from all LBW babies (LBWB) should be routinely investigated to determine the likely reason. The purpose of this study was to evaluate the pathological alterations in the placenta associated with LBWB. Materials and Methods: This is a cross-sectional observational study performed at Dhulikhel Hospital, Kathmandu University School of Medical Sciences, Kavre, Nepal. In this study, 100 placentae were included. 44 placentae from full-term delivered babies and 56 from pre-term delivered babies, all of them weighing less than 2500 gms. A gross and microscopic examination of the placentae was done. Results: 100 placentas from low-birth-weight babies were studied. Most of the mothers were in the age group of 26-30 years with primi contributing to 59%. Gross findings like infarction and calcification were noted in 8% and 29 % of the cases. Microscopic findings like Intervillous hemorrhage (44%), Syncytial knots (69%), Stromal fibrosis (24%), Basement membrane thickening (26%), Cytotrophoblastic hyperplasia (28%), Increased villous vascularity (12%), Fibrinoid necrosis (17%), Calcification (38%), Villitis (12%) and Chorangiosis (15%) were noted. Conclusion: Histopathological study together with clinical examination of placenta is simple and cost-effective technique in identifying the features present in LBWB placentae.